Research of Inverse Kinematics Algorithm of 6 DOF Manipulator based on Geometry with Arm Adjacent Three Joints Axes Parallel - Wang Yang; Wang Ben; Mai Xiaoming (Jixie chuandong)
A solving method for the inverse-kinematics （IK） problem of a kind of 6 degree of freedom （DOF） manipulator with the axes of the 3 adjacent rotational joints in the arm part，shoulder，elbow and wrist parallel is presented. The merit of this method is that，by utilizing the geometrical relation between the end-effector，hand and wrist of the manipulator determined by its structure，the position of the wrist corresponding to a desired end-effector orientation and position can be solved at the first step in the whole calculation process. And then，the solution of a 6-variable equations，which describes the relationship between the 6 joint positions of the manipulator and its end-effector orientation and position is reduced into two 3-variable equations，one of which describes the relationship between the wrist position and the positions of 3 joints distributed in the shoulder and elbow，and the other describes the relationship between the end-effector orientation and the positions of the rest 3 joint distributed in the wrist. This method reduces the complexity of solving the IK problem of a 6 DOF manipulator. The experiment results with an UR3 manipulator shows that，the method is able to compute the joints positions，in comparison with by applying the algorithm of the UR3 controller，the end-effector positioning accuracy of the manipulator by applying the presented method is up to millimeter-scale in linear and 1 degree in angular.